MicroRNA roles in regeneration: Multiple lessons from zebrafish - Ribeiro, Amanda Oliveira [UNESP]; de Oliveira, Arthur Casulli [UNESP]; Costa, Juliana Mara [UNESP]; Nachtigall, Pedro Gabriel [UNESP]; Herkenhoff, Marcos Edgar [UNESP]; Campos, Vinicius Farias; Delella, Flávia Karina [UNESP]; Pinhal, Danillo [UNESP] (Wiley, 2022)
MicroRNAs (miRNAs) are small noncoding RNAs with pivotal roles in the control of gene expression. By comparing the miRNA profiles of uninjured vs. regenerating tissues and structures, several studies have found that miRNAs are potentially involved in the regenerative process. By inducing miRNA overexpression or inhibition, elegant experiments have directed regenerative responses validating relevant miRNA-to-target interactions. The zebrafish (Danio rerio) has been the epicenter of regenerative research because of its exceptional capability to self-repair damaged tissues and body structures. In this review, we discuss recent discoveries that have improved our understanding of the impact of gene regulation mediated by miRNAs in the context of the regeneration of fins, heart, retina, and nervous tissue in zebrafish. We compiled what is known about the miRNA control of regeneration in these tissues and investigated the links among up-regulated and down-regulated miRNAs, their putative or validated targets, and the regenerative process. Finally, we briefly discuss the forthcoming prospects, highlighting directions and the potential for further development of this field.
Keywords: fins; heart; miRNAs; nervous tissue; retina